Kemampuan Regulasi Diri Siswa dan Dampaknya Terhadap Prestasi Belajar Matematika - Kusaeri Kusaeri; Umi Nida Mulhamah (JRPM (Jurnal Review Pembelajaran Matematika), 2016)
Self-regulation integrate many things of learning theories and can guide the students to strive to achieve learning goals by controlling the thoughts, behaviors, and emotions. This study aims to determine the theoretical models, testing them with empirical data, and finding influence between the ability of self-regulation to mathematics achievement. The ability of self-regulation measures consists of metacognition, motivation, and behavior. The field research with verification approach was conducted in MTsN Tanjunganom Nganjuk. The total sample is 112 students. The instrument is form of questionnaires. Mathematics achievement is taken from value data of middle semester of 2015/2016 academic year. The data were analyzed by LISREL software version 9.2 through statistical methods of Confirmatory Factor Analysis. The results shows that the theoretical model developed the show compliance with the criteria suitability test conducted. The test matches in accordance with the criteria of Goodness of Fit is a p-value and RMSEA.